Constructing channel-mediated facilitated transport membranes by incorporating covalent organic framework nanosheets with tunable microenvironments. Issue 16 (2nd April 2019) - Wang, Meidi; Pan, Fusheng; Yang, Hao; Cao, Yu; Wang, Hongjian; Song, Yimeng; Lu, Zean; Sun, Mingze; Wu, Hong; Jiang, Zhongyi
Abstract : Facilitated transport membranes with tunable microenvironments are fabricated via incorporation of metal-ion loaded COF nanosheets for gasoline desulfurization. Abstract : Inspired by the efficient facilitated diffusion via carrier proteins in biological membranes, facilitated transport membranes with synthetic carriers have been fabricated to enhance the separation performance via carrier-penetrant reversible reactions. Constructing highly ordered channels for the facilitated transport process in such membranes is favorable for achieving high efficiency, but reports are quite rare. Herein, crystalline porous covalent organic framework nanosheets (CONs) with regular pore structures, were used to load transition metal ions (typical carriers for unsaturated molecules) on their pore wall to enable a facilitated transport process in ordered channels. The physicochemical properties of the channels were elucidated by the CON microenvironments including the physical microenvironment (pore size) and the chemical microenvironment (carrier amount and carrier type). The microenvironment–performance relationship of the membranes was explored. The optimized facilitated transport membranes exhibited promising separation performance for gasoline desulfurization with a permeation flux of 21.6 kg m −2 h −1 and an enrichment factor of 6.29. Long-term operational stability and enhanced anti-swelling properties manifested superior stability of the resulting membranes.